Lo Schiavetto (1612) Travestied Sound, Ethnic Performance, and the Eloquence of the Body - Wilbourne, Emily (American Musicological Society], [Richmond (Va), 2010)
RESUMEN: This article examines at the relationship between epistemologies of sound, repertoires of popular music, and markers of ethnic difference in early seventeenth-century Italy. The analysis concentrates on two scenes from the 1612 commedia dell'arte play Lo Schiavetto ("The Little Slave"). In one, an Italian nobleman disguises himself as a mute Jew, in the other, a young Italian noblewoman sings while cross-dressed as a black, male slave. Questions of embodiment are considered, as are the specific historical circumstances of the work's original performers, Virginia Ramponi Andreini, detta Florinda, and her husband, Giovan Battista Andreini, detto Lelio. Musical discussion focuses on the genre of the madrigal comedy (with particular attention to Orazio Vecchi's L'Amfiparnaso) and Giulio Caccini's Le nuove musiche e nuova maniera di scriverle (1614).